MEMBANGUN SINERGITAS EKSEKUTIF-LEGISLATIF DI JAWA TENGAH - Abdulrahman, Wahid (JURNAL ILMU SOSIAL, 2016)
The position of the Regional Representatives Council (DPRD) and the regional head (executive) as partner makes their relationship very important for the success of the regional administration. Harmonious synergy between the two can make local governance objectives achieved effectively and efficiently. This paper reviews the executive and legislative relations in Central Java after a year leadership of Governor Ganjar Pranowo that can be learned by other region.